Significant coercivity enhancement of hot-deformed bulk magnets by two-step diffusion process using a minimal amount of Dy. (December 2021) - Korent, M.; Tang, Xin; Sepehri-Amin, H.; Hioki, K.; Soderžnik, K.Ž.; Kobe, S.; Ohkubo, T.; Hono, K.
Abstract: This work has demonstrated that a high coercivity of 2.5 T can be achieved in a 5.6-mm-thick Nd-Fe-B anisotropic magnet by applying the two-step diffusion process using Nd50 Dy30 Cu20 and Nd80 Cu20 eutectic alloys to a Dy-free Nd-Fe-B hot-deformed magnet. This is in contrast to the fact that about 5 wt.% Dy was needed to reach this coercivity level in sintered magnets. The overall Dy concentration in the sample was determined to be only 0.45 wt.% Dy, which is about 10 % of that used in the conventional Dy-alloyed sintered magnets with a comparable coercivity. Due to the low Dy concentration, a relatively high remanence of 1.32 T is retained even after the two-step diffusion process with an excellent temperature coefficient of coercivity of –0.41 %/°C. Graphical abstract: Image, graphical abstract